2002
DOI: 10.1364/josaa.19.000215
|View full text |Cite
|
Sign up to set email alerts
|

Cone photopigment in older subjects: decreased optical density in early age-related macular degeneration

Abstract: We measured changes to cone photoreceptors in patients with early age-related macular degeneration. The data of 53 patients were compared with normative data for color matching measurements of long-and middle-wavelength-sensitive cones in the central macula. A four-parameter model quantified cone photopigment optical density and kinetics. Cone photopigment optical density was on average less for the patients than for normal subjects and was uncorrelated with visual acuity. More light was needed to reduce the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
3
26
0
1
Order By: Relevance
“…the foveal birefringence is due to the radial order of the photoreceptor axons. [38][39][40][41] For good visual performance, the status of the inner retina and ocular media is important as well. Only three cases in our sample presented with poor visual acuity and a regular bowtie.…”
Section: Discussionmentioning
confidence: 99%
“…the foveal birefringence is due to the radial order of the photoreceptor axons. [38][39][40][41] For good visual performance, the status of the inner retina and ocular media is important as well. Only three cases in our sample presented with poor visual acuity and a regular bowtie.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the contrary has been shown in a number of studies which report poor correlations between drusen and kinetic measures such as dark-adaptation or glare recovery. [46][47][48] Elsner and Burns 20 hypothesized that decreased photosensitivity did not imply primary damage to Bruch's membrane. They used colour match techniques and demonstrated that decreased photosensitivity of the cone photopigment was not correlated with slowed regeneration kinetics in early ARM.…”
Section: Psychophysical and Electrophysiological Function Tests In Armmentioning
confidence: 99%
“…It is still not clear whether functional deficits in early ARM measured with various psychophysical tests are primarily caused by reduced sensitivity of photoreceptors, [20][21][22][23] by postreceptoral damage 21,24,25 or by damage to other tissues involved in ARM such as the RPE/Bruch's membrane complex 10,11,26 or the choroid. [27][28][29][30][31] Knowledge of the primary retinal site affected by ARM would be helpful in targeting the application of future treatments, such as pharmaceuticals, retinal transplants, or computer chips.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, although the parafovea in humans is reduced in thickness with age, the foveola remains unchanged (Kanai et al, 2002) and the number of foveal cones remains stable (Curcio, 2001). Furthermore, although the amount of pigment appears to be reduced in aged patients (Elsner et al, 2002), Fortune and Johnson (2002) have suggested that changes in cone responsiveness are mainly due to pre-retinal optical factors. Thus, in human subjects, rods are susceptible to age-related degeneration, whereas cones are more stable.…”
Section: The Aging Mouse Retina As a Model System For Normal Human Agingmentioning
confidence: 99%